Connecting Hodge and Sakaguchi-Kuramoto through a mathematical framework for coupled oscillators on simplicial complexes - Alexis Arnaudon; Robert L. Peach; Giovanni Petri; Paul Expert (Communications Physics, 2022)
Synchronization dynamics in the presence of higher order interactions is well represented through variations of the Kuramoto model and subject of current interest. Here, the authors study and characterize the behavior of the simplicial Kuramoto model with weights on any simplices and in the presence of linear and nonlinear frustration, defined as the simplicial Sakaguchi-Kuramoto model.